Fostering Ethical Values in Islamic Education through Arabic Language Learning: A Conceptual Integration - Nafiatur Rasyidah; Muhammad Fadli Ramadhan (Fakultas Agama Islam Universitas Billfath, 2025)
This study explores the integration of Islamic educational ethics in Arabic language learning, highlighting essential ethical values for both teachers and students. Through a qualitative library research approach this article aims to understand 2 things. First, how the concept of educational ethics in the Islamic view; and second, how to integrate the concept of educational ethics in the Islamic view with Arabic language learning. Data is obtained through in-depth literacy studies on literature sources in the form of books and scientific articles related to ethical theory in Islam and Islamic education. The resulting data is then analyzed with data condensation, then presenting the data, and finally drawing conclusions. From the results of the literature review conducted, it was found that in the learning process, Islam regulates ethical aspects that must be applied primarily by students and teachers in the teaching and learning process in the classroom such as first, in terms of students: (1) Respect for the teacher; (2) Confident in the teacher's knowledge; (3) Tawadhu'; (4) Patience; (5) Obey; (6) Patience and Tenacity; (7) Sincerity in seeking knowledge; (8) Position the teacher as an example; and second, in terms’s of teacher: (1) Teaching with the sincere intention of seeking the pleasure of Allah; (2) Intend to spread knowledge; (3) Uphold the truth and broadcast falsehood; (4) Always pray for his disciples; (5) Use language that is easy for students to digest; (6) Show concern for each student; (7) Be well-groomed and purify first; (8) Get used to prayer when starting learning; (9) Reflect at the end of each lesson; (10) Carry out evaluations authentically; (11) Position oneself as an example that can be emulated by his students. The integration of all these points in Arabic language learning shows a close and crucial relationship in an effort to bring fun, quality, and meaningful learning for students.